236PClinical decision making and multidisciplinary team meetings (MDMs) in early breast cancer. Is the agreement between planned and applied therapeutic program?. (1st October 2019) - Giavarra, M; Bertoli, E; Buoro, V; Zara, D; Targato, G; Palmero, L; Vitale, M G; Pelizzari, G; Basile, D; Gerratana, L; Bonotto, M; Andreetta, C; et al.
Abstract: Background: Cancer multidisciplinary team meetings (MDMs) are commonly acknowledged as a good clinical practice. One of the roles of MDMs is to identify the best diagnostic and therapeutic strategies for patients (pts) with new diagnosis of early breast cancer (EBC). In this setting, the purpose of the study was to define whether there was agreement between the planned program (i.e. MDMs-based decision) and that actually applied (i.e. actual therapeutic choice, ATC). In addition, the study explored factors associated with discordance. Methods: We conducted a monocentric retrospective study of a consecutive series of 291 pts with new diagnosis of EBC, discussed at MDMs at the University Hospital of Udine (Italy), from January 2017 to June 2018. Results: Median age was 62 years (range 27-88 years). Among invasive EBC patients, the most frequent phenotype was luminal-A (38%), followed by luminal-B (33%), HER2-positive (12%) and triple negative (5%). Thirty-four pts (12%) had diagnosis of in situ carcinoma (DCIS). Median time from MDMs discussion to first oncological examination was two weeks. Rate of discordance between MDMs-based decision and final choice, during face to face consultation with the oncologist, was 15.8% (46/291). Among cases with discordance, 19 pts (41.3%) had age > 70 years; 8 pts (17%) had a diagnosis of DCIS, 13 pts (28%) luminal-B carcinoma, 12 pts (26%) luminal-A, 9 pts (20%) HER2-positive and 4 pts (9%) triple negative EBC. The most frequent reason for changing the MDMs-based program was clinical decision by the oncologist at the first evaluation (87%). Follow-up was preferred to the chemotherapy proposed within the MDMs by 15% of pts, and to the endocrine therapy in 39% cases (among these, 44.5% had diagnosis of DCIS). In our study 16/46 pts (35%) had a therapeutic change from chemotherapy to endocrine therapy: among these pts, 7/16 had a luminal-B and 6/16 had a HER2-positive disease. Further analysis aiming at evaluating variables which could predict discordance between MDMs proposal and face to face oncological consultation are ongoing. Conclusions: The results of our study could be useful for enhance the role of MTD and identify unmet needs in decision making process in EBC. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.